2004
DOI: 10.1111/j.1368-5031.2004.0018.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of CD7 and CD56 antigens in acute leukaemias

Abstract: The prognostic significance of immunophenotypical properties of leukaemic cells is well known. However, the biological and clinical significance of CD7 and CD56 antigen expression in acute leukaemias are not clearly established. In patients with acute leukaemias, we identified CD7 and CD56 expression and analysed their associations with markers expressed early in haemopoietic ontogeny and clinical parameters. Among 22 patients with acute leukaemia [12 acute myeloblastic leukaemia (AML), 10 acute lymphoblastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Saxena et al, [6] found that CD7 expression in AML is associated with the immature antigens CD34, HLA-DR, and TdT, these findings are in accordance with our results except for TdT which was negative, they also contend that AML with CD7 may originate from early hematopoietic precursors and indicate biologic aggressiveness in a significant proportion of patients. Tiftik et al, [19] found CD7 positivity in 7 of 12 AML patients and CD56 expression in 3 AML patients and revealed that CD7 and CD56 expression at diagnosis was associated with a low remission rate and biological aggressiveness in AML patients. Suzuki et al, [20] revealed poor prognosis in AML in which CD7 and CD56 were aberrantly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Saxena et al, [6] found that CD7 expression in AML is associated with the immature antigens CD34, HLA-DR, and TdT, these findings are in accordance with our results except for TdT which was negative, they also contend that AML with CD7 may originate from early hematopoietic precursors and indicate biologic aggressiveness in a significant proportion of patients. Tiftik et al, [19] found CD7 positivity in 7 of 12 AML patients and CD56 expression in 3 AML patients and revealed that CD7 and CD56 expression at diagnosis was associated with a low remission rate and biological aggressiveness in AML patients. Suzuki et al, [20] revealed poor prognosis in AML in which CD7 and CD56 were aberrantly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…CD56, also called neural cell adhesion molecule, is a binding glycoprotein normally expressed on the surface of neurons, glia, skeletal muscle, and natural killer cells. Interestingly, CD56 expression is associated with high rates of extramedullary disease, including CNS, low CR rate, and poor overall survival [8, 9]. Flow cytometry of bone marrow at diagnosis revealed that our patient's blast cells were positive for the CD56 molecule.…”
Section: Discussionmentioning
confidence: 93%
“…However, there are data suggesting that CNS infiltration with acute myeloid leukemia is indicative of poor prognosis [9], which means that early diagnosis and treatment are more than necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Certain immunophenotypic marker combinations have been suggested as being specific for a genetic aberrancy and/or prognosis, but the practical use of these combinations remains to be elucidated . As an example co‐expression of CD56 and CD7 has been associated with a poor prognosis , a finding we could not reproduce in our cohort (data not shown).…”
Section: Discussionmentioning
confidence: 94%